Genomic and transcriptomic insights into the thermo-regulated biosynthesis of validamycin in Streptomyces hygroscopicus 5008 - Wu Hang; Qu Shuang; Lu Chenyang; Zheng Huajun; Zhou Xiufen; Bai Linquan; Deng Zixin (BMC Genomics, 2012)
Abstract Background Streptomyces hygroscopicus 5008 has been used for the production of the antifungal validamycin/jinggangmycin for more than 40 years. A high yield of validamycin is achieved by culturing the strain at 37°C, rather than at 30°C for normal growth and sporulation. The mechanism(s) of its thermo-regulated biosynthesis was largely unknown. Results The 10,383,684-bp genome of strain 5008 was completely sequenced and composed of a linear chromosome, a 164.57-kb linear plasmid, and a 73.28-kb circular plasmid. Compared with other Streptomyces genomes, the chromosome of strain 5008 has a smaller core region and shorter terminal inverted repeats, encodes more α/β hydrolases, major facilitator superfamily transporters, and Mg2+/Mn2+-dependent regulatory phosphatases. Transcriptomic analysis revealed that the expression of 7.5% of coding sequences was increased at 37°C, including biosynthetic genes for validamycin and other three secondary metabolites. At 37°C, a glutamate dehydrogenase was transcriptionally up-regulated, and further proved its involvement in validamycin production by gene replacement. Moreover, efficient synthesis and utilization of intracellular glutamate were noticed in strain 5008 at 37°C, revealing glutamate as the nitrogen source for validamycin biosynthesis. Furthermore, a SARP-family regulatory gene with enhanced transcription at 37°C was identified and confirmed to be positively involved in the thermo-regulation of validamycin production by gene inactivation and transcriptional analysis. Conclusions Strain 5008 seemed to have evolved with specific genomic components to facilitate the thermo-regulated validamycin biosynthesis. The data obtained here will facilitate future studies for validamycin yield improvement and industrial bioprocess optimization.